IMPLEMENTASI e-KTP DI KECAMATAN NGABANG KABUPATEN LANDAK - Christian Suganda Bayu Patra E.42008049 (FISIP Universitas Tanjungpura Pontianak, 2012)
AbstractThesis writing is meant to find a solution to solving the problems faced by the Pemerintah Kecamatan Ngabang especially and Pemerintah Kabupaten Landak generally associated implementation processes Presidential Decree No. 35 Year 2010 on National Identity Card-Based Identification Number Population Nationally. The formulation of the research problem is how the process of implementation of e-KTP cards in Kecamatan Ngabang Kabupaten Landak. The conclusion of this study is that there are 3 elements in the process of policy implementation of e-KTP cards in Kecamatan Ngabang Kabupaten Landak: (1) implementing elements (implementor) consists of Dinas Kependudukan dan catatan Sipil Kabupaten Landak, Pemerintah Kecamatan Ngabang, Lower Village Government Offices, (2) program elements are formatted through Presidential Decree No. 35 Year 2010 concerning the implementation of a national ID card based NIK (3) elements of the target group (the target group) that people in Kecamatan Ngabang. The geographical conditions shelter residents also describe the process of policy implementation. Then, communication and socialization factors likely to affect the process of policy implementation tersebut.Saran of this research is Dinas Kependudukan dan catatan Sipil Kabupaten Landak, Pemerintah Kecamatan Ngabang, dan Pemerintah Desa Hilir Kantor need to enhance cooperation in the implementation of e-KTP card policy and subsequent policies in Kecamatan Ngabang. Moreover, people also need to continue to support than policies made and implemented by the local government. Local Government and District Governments need to improve communication between organizations, including adding personnel quality.Keyword (Key Word): Implementation, Policy, Presidential Decree No. 35 Year 2010.